2017
DOI: 10.1038/s41598-017-15322-8
|View full text |Cite
|
Sign up to set email alerts
|

Various response of Pinus tabulaeformis Carr. regeneration in artifical gaps

Abstract: Understanding the influence of gaps in promoting canopy recruitment will help to maintain structural stability and achieve continuous forest cover. We established three control plots and experimental plots with three replications each (gap sizes L-I, L-II, L-III, and L-IV) in a Chinese pine (Pinus tabulaeformis Carr.) plantation to test the short-term effects of gap size on the age distribution, density and growth, and annual height and ground diameter growth for regeneration established before (REBG) and afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Gap formation is beneficial for the management of Pinus tabulaeformis plantations [12]. Previous studies reported that gap creation positively influenced Chinese pine seeding regeneration [13][14][15]. However, there have been few studies regarding the changes of soil microbial communities and enzyme activities after gap creation in a Pinus tabulaeformis forest.…”
Section: Introductionmentioning
confidence: 99%
“…Gap formation is beneficial for the management of Pinus tabulaeformis plantations [12]. Previous studies reported that gap creation positively influenced Chinese pine seeding regeneration [13][14][15]. However, there have been few studies regarding the changes of soil microbial communities and enzyme activities after gap creation in a Pinus tabulaeformis forest.…”
Section: Introductionmentioning
confidence: 99%